2016
DOI: 10.18632/oncotarget.13255
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal adipose tissue thickness measured using magnetic resonance imaging is associated with lumbar disc degeneration in a Chinese patient population

Abstract: The relationship between abdominal adiposity and disc degeneration remains largely uninvestigated. Here, we investigated the association between abdominal adipose tissue thickness and lumbar disc degeneration in a cross-sectional study of 2415 participants from The Second Affiliated Hospital of Wenzhou Medical University. All subjects were scanned with a 3T Magnetic Resonance Imaging system to evaluate the degree of lumbar disc degeneration. Multiple logistic regression analysis revealed that men in the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
7
3
Order By: Relevance
“…Several mechanisms might contribute to the association between the abdominal fat tissue diameter and lumbar disk degeneration. Accumulation of fat might increase compressive and shear loads on the lumbar spine during activities of daily living, and also atherosclerosis and stenosis of the feeding arteries might also occur and then reduce blood flow, resulting in disk degeneration and LBP . However, the results of this study showed that the abdominal subcutaneous fat dimension was larger (22%–29%) in the patients with LBP than the healthy participants.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Several mechanisms might contribute to the association between the abdominal fat tissue diameter and lumbar disk degeneration. Accumulation of fat might increase compressive and shear loads on the lumbar spine during activities of daily living, and also atherosclerosis and stenosis of the feeding arteries might also occur and then reduce blood flow, resulting in disk degeneration and LBP . However, the results of this study showed that the abdominal subcutaneous fat dimension was larger (22%–29%) in the patients with LBP than the healthy participants.…”
Section: Discussioncontrasting
confidence: 63%
“…Accumulation of fat might increase compressive and shear loads on the lumbar spine during activities of daily living, and also atherosclerosis and stenosis of the feeding arteries might also occur and then reduce blood flow, resulting in disk degeneration and LBP. 39 However, the results of this study showed that the abdominal subcutaneous fat dimension was larger (22%-29%) in the patients with LBP than the healthy participants. One of the main causes of such a difference might an increase in the size of abdominal noncontractile tissues.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…associations between fat mass and pain [50,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], nine studies examined adiposity within a specific muscle [68][69][70][71][72][73][74][75], five studies did not specify a site of pain [76][77][78][79], two studies only examined multisite pain [80,81], and three studies examined pain in children [82][83][84].…”
Section: Plos Onementioning
confidence: 99%
“…1,2 Various studies have been published regarding the association between degenerative spinal diseases and the parameters, such as the body mass index (BMI), para-spinal fat content, and epidural lipomatosis. 1,[3][4][5][6][7][8] Since the vertebral column together with its muscles and ligaments is the load-bearing structure of the body, any increase in the load will probably affect its fate. BMI is a relatively simple measurement but still requires the patient's weight and height values to be calculated, which might add limitations to a retrospective study.…”
Section: Introductionmentioning
confidence: 99%